Application of vertebral body compression osteotomy in pedicle subtraction osteotomy on ankylosing spondylitis kyphosis: Finite element analysis and retrospective study - Yang, Canchun; Zeng, Ziliang; Yan, Haolin; Wu, Jionglin; Lv, Xin; Zhang, Di; Zhang, Zhilei; Jiang, Xu; Zhang, Chi; Fu, Guo; Peng, Xiaoshuai; Wang, Zheyu; et al. (Frontiers in Endocrinology, 2023)
Background: Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease, with pathological characteristics of bone erosion, inflammation of attachment point and bone ankylosis. Due to the ossified intervertebral disc and ligament, pedicle subtraction osteotomy (PSO) is one of mainstream surgery of AS-related thoracolumbar kyphosis, but the large amount of blood loss and high risk of instrumental instability limit its clinical application. The purpose of our study is to proposed a new transpedicular vertebral body compression osteotomy (VBCO) in PSO to reduce blood loss and improve stability. Methods: A retrospective analysis was performed on patients with AS-related thoracolumbar kyphosis, underwent 1-level PSO in our hospital from February 2009 to May 2019. 31 patients were included in this study, 6 received VBCO and 25 received eggshell vertebral body osteotomy. We collected demographic data containing gender and age at diagnosis. Surgical data contained operation time, estimated blood loss (EBL) and complications. Radiographic data contained pre-operative and follow-up sagittal parameters including chin brow-vertical angle (CBVA), global kyphosis (GK), thoracic kyphosis (TK) and lumbar lordosis (LL). A typical case with L2-PSO was used to establish a finite element model. The mechanical characteristics of the internal fixation device, vertebral body and osteotomy plane of the two osteotomy models were analysed under different working conditions Results: The VBCO could provide comparable restorage of CBVA, GK, TK, LL to eggshell osteotomy procedure (all p >0.05). The VBCO significantly reduced EBL than those with eggshell osteotomy [800.0 ml (500.0–1439.5 ml) vs. 1455.5 ml (1410.5–1497.8 ml), p=0.033]. Compared with the eggshell osteotomy, VBCO showed better mechanical property. For the intra-pedicular screw fixation, the VBCO group had a more average distributed and lower stress condition on both nails and connecting rod. And VBCO had a flattened osteotomy plane than the pitted osteotomy plane of eggshell group, showing a lower and more average distributed maximum stress and displacement of osteotomy plane Conclusions: In our study, we introduced VBCO as an improved method in PSO, with advantages in reducing blood loss and providing greater stability. Further investigation should focus on clinical research and biomechanical analysis for the application of VBCO.